2012
DOI: 10.1097/ccm.0b013e3182416f23
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness from 2009 pandemic influenza A virus and bacterial coinfection in the United States*

Abstract: Objective The contribution of bacterial co-infection to critical illness associated with 2009 influenza A (H1N1) [pH1N1] virus infection remains uncertain. The objective of this study was to determine if bacterial co-infection increased the morbidity and mortality of pH1N1. Design Retrospective and Prospective cohort study Setting 35 adult U.S. intensive care units over the course of one year Patients 683 critically ill adults with confirmed or probable pH1N1 Interventions None Measurements and Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
298
6
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 351 publications
(348 citation statements)
references
References 35 publications
16
298
6
10
Order By: Relevance
“…It is highly probable that the mechanism explaining the higher mortality is due to either to the bacterial infection itself or to an association of virulence factors from both virus and bacteria. Lastly, as shown in this paper and others, the epidemiology of pathogens responsible for co-infection is regional and likely depends on many local factors, but may also be subject to change over time, with emergence in the community of pathogens usually seen in nosocomial infections [6,7,9,12].…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…It is highly probable that the mechanism explaining the higher mortality is due to either to the bacterial infection itself or to an association of virulence factors from both virus and bacteria. Lastly, as shown in this paper and others, the epidemiology of pathogens responsible for co-infection is regional and likely depends on many local factors, but may also be subject to change over time, with emergence in the community of pathogens usually seen in nosocomial infections [6,7,9,12].…”
mentioning
confidence: 81%
“…Similar to previously reported data from this group [5], Streptococcus pneumoniae was the predominant pathogen recovered, followed by Pseudomonas aeruginosa and methicillin-susceptible Staphylococcus aureus (MSSA). Not unexpectedly, data from the USA found that S. aureus was the predominant organism, with a higher prevalence of methicillin-resistant S. aureus (MRSA) [6]. Interestingly, the authors found an apparent increased rate of co-infection over time (from 11.4% in 2009 to 23.4% in 2015), without clear explanation.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…During the 2009 A/H1N1 influenza pandemic, bacterial co-infections complicated up to one-third of influenza cases in the United States in which S. aureus was the most common pathogen, accounting for 27% of the cases in both critically ill children and adults [25,26]. S. aureus co-infection was associated with significantly higher morbidity and mortality [26]. To date, the clinical association between the healthy carriage of S. aureus and the secondary staphylococcal pneumonia is still unclear.…”
Section: Impact Of Viral Infections In the Respiratory Tract On Staphmentioning
confidence: 99%